DIALECT CLASSIFICATION AND PHONETIC CHARACTERISTICS OF UZBEK DIALECTS IN THE SURKHANDARYA REGION - Temirova, Hayotxon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study ehamines the phonetic classification of Uzbek dialects in Surkhandarya, especially the "j" and "y" groups. Despite contributions by Russian and Uzbek linguists, no unified classification exists. The paper reviews works by Polivanov, Borovkov, and G‘ozi Olim Yunusov, focusing on vowel harmony, consonant variation, and bilingualism’s influence.